Microbial ecosystem assessment and hydrogen oxidation potential of newly discovered vent systems from the Central and South-East Indian Ridge - Adam-Beyer, Nicole; Laufer-Meiser, Katja; Fuchs, Sebastian; Schippers, Axel; Indenbirken, Daniela; Garbe-Schönberg, Dieter; Petersen, Sven; Perner, Mirjam (Frontiers in Microbiology, 2023)
In order to expand the knowledge of microbial ecosystems from deep-sea hydrothermal vent systems located on the Central and South-East Indian Ridge, we sampled hydrothermal fluids, massive sulfides, ambient water and sediments of six distinct vent fields. Most of these vent sites were only recently discovered in the course of the German exploration program for massive sulfide deposits and no previous studies of the respective microbial communities exist. Apart from typically vent-associated chemosynthetic members of the orders Campylobacterales, Mariprofundales, and Thiomicrospirales, high numbers of uncultured and unspecified Bacteria were identified via 16S rRNA gene analyses in hydrothermal fluid and massive sulfide samples. The sampled sediments however, were characterized by an overall lack of chemosynthetic Bacteria and the presence of high proportions of low abundant bacterial groups. The archaeal communities were generally less diverse and mostly dominated by members of Nitrosopumilales and Woesearchaeales, partly exhibiting high proportions of unassigned Archaea. Correlations with environmental parameters were primarily observed for sediment communities and for microbial species (associated with the nitrogen cycle) in samples from a recently identified vent field, which was geochemically distinct from all other sampled sites. Enrichment cultures of diffuse fluids demonstrated a great potential for hydrogen oxidation coupled to the reduction of various electron-acceptors with high abundances of Hydrogenovibrio and Sulfurimonas species. Overall, given the large number of currently uncultured and unspecified microorganisms identified in the vent communities, their respective metabolic traits, ecosystem functions and mediated biogeochemical processes have still to be resolved for estimating consequences of potential environmental disturbances by future mining activities.